Implementasi Serta Peran Aktif Mahasiswa dalam Memperkuat Ketahanan Nasional dan Bela Negara - inayah, dinda; Amalia, Gina (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2026)
Students are citizens who have an obligation to defend the country. Students are not only tasked as someone who seeks academic knowledge, but also students have an active role in advancing the country. This paper aims to examine the implementation of the values of state defense and the active role of students in strengthening national resilience in the digital era and globalization, using the civic communication approach as a conceptual framework. Through the literature study method, this research shows that students have a strategic role in maintaining the integrity of the Republic of Indonesia through digital innovation, information literacy, strengthening cultural identity and participation in digital socio-political movements. In addition, the civic communication approach is proven to be able to shape students' national character and increase collective awareness in defending the country actively and intelligently. The results of this study confirm that strengthening the role of students as actors of national resilience must be carried out systematically and sustainably through synergy between educational institutions, government and society.